2016
DOI: 10.4292/wjgpt.v7.i1.156
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic effect of melatonin on pediatric functional dyspepsia: A pilot study

Abstract: AIM:To study the effectiveness of melatonin vs placebo in children with functional dyspepsia (FD). METHODS:The study was conducted as a double blind, randomized, placebo controlled crossover trial. Subjects were aged 8-17 years and diagnosed with FD based on Rome Ⅲ criteria. All subjects had failed to respond to 4 wk of acid suppression. Subjects receive a continuous two weeks of placebo and a continuous two weeks of melatonin in an order blinded to the participant and the study team. A Global Clinical Score w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 16 publications
1
11
0
Order By: Relevance
“…208,209 To our knowledge, there have been 15 randomized placebocontrolled trials of medications for pediatric FAPDs. 158,[210][211][212][213][214][215][216][217][218][219][220][221][222][223] We have summarized these studies in Table 3. The current data does not lend itself to the development of pediatric practice guidelines regarding medication treatment for pediatric FAPDs as have been developed for adult IBS.…”
Section: Medicationsmentioning
confidence: 99%
“…208,209 To our knowledge, there have been 15 randomized placebocontrolled trials of medications for pediatric FAPDs. 158,[210][211][212][213][214][215][216][217][218][219][220][221][222][223] We have summarized these studies in Table 3. The current data does not lend itself to the development of pediatric practice guidelines regarding medication treatment for pediatric FAPDs as have been developed for adult IBS.…”
Section: Medicationsmentioning
confidence: 99%
“…Melatonin has been investigated as a therapeutic agent for FD and IBS, however, the efficacy remains unclear. A study on paediatric FD found that melatonin had no significant effect ( Zybach, 2016 ), however, another study found that FD participants showed significant improvement in sleep quality and abdominal pain ( Klupinska et al, 2007 ). Similarly, disturbances in melatonin metabolism and secretion have been suggested to play a role in the pathophysiology of IBS ( Radwan et al, 2009 ).…”
Section: Disorders Of Gut-brain Interactionsmentioning
confidence: 99%
“…Various treatment options are discussed further in the list below. However, in a randomized controlled trial to evaluate therapeutic effects of melatonin, it was not found to be superior to placebo in children [45]. o Cognitive behavioral therapy (CBT): The impact of an FGID on a patient's life can be directly correlated with the management of psychosocial factors.…”
Section: Treatment Optionsmentioning
confidence: 99%